2015
DOI: 10.1051/0004-6361/201424086
|View full text |Cite
|
Sign up to set email alerts
|

Planckintermediate results. XX. Comparison of polarized thermal emission from Galactic dust with simulations of MHD turbulence

Abstract: Polarized emission observed by Planck HFI at 353 GHz towards a sample of nearby fields is presented, focusing on the statistics of polarization fractions p and angles ψ. The polarization fractions and column densities in these nearby fields are representative of the range of values obtained over the whole sky. We find that: (i) the largest polarization fractions are reached in the most diffuse fields; (ii) the maximum polarization fraction p max decreases with column density N H in the more opaque fields with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…As an example, previous studies have found an inverse correlation between the polarization fractionP and the local dispersion of magnetic field orientations at several scales in molecular clouds (Planck Collaboration et al 2015a, 2015bFissel et al 2016;Koch et al 2018). Such a measure toward B1-c would support the hypothesis of a complex but unresolved polarization structure, and higher-resolution observations using interferometric facilities would provide further evidence to confirm or disprove this scenario.…”
Section: Polarization Fraction and Grain Alignmentmentioning
confidence: 72%
“…As an example, previous studies have found an inverse correlation between the polarization fractionP and the local dispersion of magnetic field orientations at several scales in molecular clouds (Planck Collaboration et al 2015a, 2015bFissel et al 2016;Koch et al 2018). Such a measure toward B1-c would support the hypothesis of a complex but unresolved polarization structure, and higher-resolution observations using interferometric facilities would provide further evidence to confirm or disprove this scenario.…”
Section: Polarization Fraction and Grain Alignmentmentioning
confidence: 72%
“…This effect likely decreased our S values compared to Planck Collaboration XIX ( 2015), but Planck Collaboration XX et al (2015) uses the same resolution of 15 as ours, and a very comparable lag scale of = 16 . This means that the difference in S values between our study and those of Planck Collaboration XX et al (2015) will be almost entirely due to the differences in masking.…”
Section: Comparison Of Polarization Propertiesmentioning
confidence: 50%
“…Magnetic field splits into the MFTs due to the Parker (1979) instability in the regions where Bt becomes larger than Bz. We assume that MFTs have the form of the torus with minor radius a mft << H and major radius ac ∼ r.…”
Section: The Stationary Velocity Of the Magnetic Flux Buoyancymentioning
confidence: 99%
“…Ohmic diffusion (OD) and magnetic ambipolar diffusion (MAD) are the main processes that constraint the generation of the magnetic field during the star and disc formation. OD of the magnetic field is caused by currents dissipation in gas with finite conductivity (see Parker (1979)). MAD is the process of plasma drift through the neutral gas under the action of the electromagnetic force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation